PENGARUH PENGGUNAAN SMARTPHONE TERHADAP PERKEMBANGAN ANAK USIA PRA SEKOLAH DI TK DAN PAUD PERMATA HATI - Khodijah, Upus Piatun; Mega, Mega; Ulfah, Erliana (Jurnal Medikes (Media Informasi Kesehatan), 2020)
One of the development information technology and communication is the development of telecomunication technology of Smartphone. The smartphone has the ability of functions and uses similarly like computer. The impacts of using Smartphone to childhood cause worriness because they are unstable enough, they have very high curiousity and influence to the effect of increasing their consumtive character. The aims of this research were to analyze the influence of using smartphone to the development of pre school aged children at Kindergarten School and Early Childhood Education of Permata Hati Cijelag, Tomo Village, Subdistrict Tomo, Sumedang Regency. This research used quantitative method. Sampling taking in this research used nonprobability sampling by using total sampling, the respondents in this research were pre school aged children in Kindergarten School and Early Childhood Education Permata Hati Cijelag, Tomo Village, Subdistrict Tomo, Sumedang Regency in 2019. The research subjects were pre school aged children in Kindergarten School and Early Childhood Education Permata Hati Cijelag, Tomo Village, Subdistrict Tomo, Sumedang Regency as many as 30 children. Statististicstesting before data analysis gained made a normality test by Saphiro Wilk, then data distributed normally thus the next test did independent t test with significance p<0,05. The research result showed that there are influences of using Smartphone to the development of pre school aged children with significant score (r) = 0,02 < 0,05. The research result showed that there are influences of using Smartphone to the development of pre school aged children.